DEVELOPMENT AGAINST THE POTENCY OF CHILDHOOD - Gama Noronha, José Eduardo (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2023)
The book ’’Right to Development’’ adds to the growing number of researches on Childhood Studies in Brazil, from a critical perspective at childhood’s rights and the concept of development. Fruit of the author’s doctoral thesis, the work bases itself in Foucault’s genealogy to return to the legal, historical paths and forces in dispute around the concept of development as a key to understanding the juridical-political subjectivities of children and adolescents. Standing out from other works that deal with the articulation between childhood and law, guided mainly by the protective bias, the key here is to found a new understanding of subjects of rights based on post-structuralist authors and consolidate the importance of political participation of children and young people as possible, necessary and legitimate.